The Enactment of the Colombian National Bilingual Program: Equal Access to Language Capital? - Diego Cardona-Escobar; Melissa Barnes; Marc Pruyn (Universidad Nacional de Colombia, 2023)
Drawing upon Bourdieu's concept of capital, this article examines the enactment of the Programa Nacional de Bilingüismo (National Bilingual Program), a policy that aims to provide Colombian students equal opportunities to learn English. In this exploratory, sequential mixed-methods study, data were collected from teachers and students from three Grade 5 classrooms of public schools in Colombia. The findings revealed that the plan's differentiated enactment generates unequal access to opportunities to build language capital and unequal levels of academic language achievement among the three schools. We argue that the enactment of the plan to equalize opportunities and achievement and therefore build the language capital of Colombian students is obstructed by existing funding structures.